Prevalence of Hypertension in Diabetes - Bharat La!, Mujhahid All Chnadio, Naveed Sattar, Tabinda Taqi, Salma Memon (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2018)
Objective: To know the prevalence of hypertension in diabetes in our setup. Methods: This descriptive cross-sectional study was conducted at diabetic clinic sponsored by Rotary club Nawabshah from Feb 2016 to Feb 2017 where 150 patients were examined. After taking consent of patient. demographic data was collected. it included age. duration of diabetes, history of hypertension. weight & height. Blood Pressure was measured by sphygmomanometer. Result: Seventy eight out of 150 subjects had hypertension ;living prevalence rate of 52%. Two out of eight (25%) type’ subject had hypertension while SeVelliy SI out of 142 (53.25%) type2 diabetes had hypertension. Conclusion: Prevalence of hypertension in diabetes is high leading to many complications. Strict control of hypertension can prevent these complications.